Cobalt-rich hydroxide and preparation method thereof, cobalt-coated positive electrode material and preparation method thereof, and lithium ion battery
By using cobalt-rich hydroxide as the coating material, the problems of uneven coating and degraded capacity performance are solved, and uniform surface coating of the positive electrode material and improved battery performance are achieved.
Patent Information
- Application Number
- CN202411996478.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The poor dispersion of the particles of the existing cladding materials leads to uneven coating, and the capacity performance of the battery prepared by the coated positive electrode material is deteriorated.
Cobalt-rich hydroxide is used as the coating material to improve its dispersion performance and coating uniformity by adjusting its agglomeration coefficient, specific surface area, average grain size and agglomeration state.
The surface of the positive electrode material is uniformly coated, which improves the cycling performance and capacity retention rate of the battery, and reduces the amount of residual alkali on the surface and the generation of side reactions.
Smart Images

Figure CN119797450A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a cobalt-rich hydroxide and a preparation method thereof, a cobalt-coated positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries are widely used in electronic portable devices, electric vehicles, wearable electronic products, medical equipment and other fields due to their high energy density and high conversion efficiency. In current lithium-ion battery technology, the positive electrode material is the key to determining the battery cost and energy density. Therefore, the development of positive electrode materials is crucial to the successful application of lithium-ion batteries. However, the positive electrode material is easy to break during the operation of the battery, and there are continuous side reactions between it and the electrolyte, which has a great impact on the performance of the battery.
[0003] In order to improve the performance of the positive electrode material, the positive electrode material will be coated. The coating agent needs to be coated on the surface of the positive electrode material. The particle size of the coating agent is generally small, and the particles are prone to spontaneous agglomeration, resulting in poor particle dispersion. The coating on the surface of the positive electrode material is prone to uneven coating, which affects the electrochemical performance of the battery prepared later.
[0004] In addition, commonly used coating materials are generally metal oxides, such as Al2O3, ZrO2, TiO2, La2O3 and other non-electrochemically active agents; non-electrochemically active agents can serve as a physical barrier between the positive electrode material and the electrolyte, reducing the interface side reactions. However, due to the non-conductivity of electrons and ions of these metal oxides, the capacity performance of the battery prepared from the coated positive electrode material will be affected.
[0005] How to improve the dispersion performance of coating materials to improve coating uniformity, and enhance the capacity performance of batteries made from coated positive electrode materials, is still a challenge faced by currently used coating materials. Summary of the invention
[0006] The purpose of the present application is to provide a cobalt-rich hydroxide and a preparation method thereof, a cobalt-coated positive electrode material and a preparation method thereof, and a lithium-ion battery, aiming to solve the problem of uneven coating caused by poor dispersion of existing coating material particles, and the problem of decreased capacity performance of batteries prepared from coated positive electrode materials.
[0007] To achieve the above objectives, in a first aspect, the present application provides a cobalt-rich hydroxide, the agglomeration coefficient of the cobalt-rich hydroxide is in,
[0008] d BET =6 / (ρ·BET),
[0009] ρ is the true density of the cobalt-rich hydroxide,
[0010] BET is the specific surface area of the cobalt-rich hydroxide,
[0011] It is the average crystallite size of the cobalt-rich hydroxide calculated when the X-ray diffraction test is performed using Cu-Kα rays.
[0012] In some embodiments, the cobalt-rich hydroxide satisfies at least one of the following conditions:
[0013] A. Agglomeration coefficient of the cobalt-rich hydroxide
[0014] B. The specific surface area of the cobalt-rich hydroxide is 30 m 2 / g-45m 2 / g;
[0015] C. The cobalt-rich hydroxide BET =6 / (ρ·BET)=34nm-65nm;
[0016] D. Average grain size of the cobalt-rich hydroxide 30nm-45nm;
[0017] E. Average grain size of the cobalt-rich hydroxide is the average grain size on the (001) crystal plane, (100) crystal plane, (101) crystal plane, (002) crystal plane, (102) crystal plane, (110) crystal plane, (003) crystal plane, (111) crystal plane, (200) crystal plane, (103) crystal plane, (201) crystal plane, (202) crystal plane, and (112) crystal plane.
[0018] In some embodiments, the agglomeration state Hausner ratio of the cobalt-rich hydroxide is 2.0-3.0, wherein the tap density TD of the cobalt-rich hydroxide is 0.50 g / cm 3 -0.85g / cm 3 The bulk density AD of the cobalt-rich hydroxide is 0.20 g / cm 3 -0.50g / cm 3 .
[0019] In some embodiments, the cobalt-rich hydroxide satisfies at least one of the following conditions:
[0020] A. In the X-ray diffraction pattern of the cobalt-rich hydroxide, the peak intensity I of the diffraction peak corresponding to the (001) crystal plane is (001) The peak intensity I of the diffraction peak corresponding to the (101) crystal plane is (101) The peak intensity ratio I (001) / I (101)is 1.3 - 1.8;
[0021] B. The average particle size D50 of the cobalt-rich hydroxide is 0.3 - 1.0 μm;
[0022] C. The chemical formula of the cobalt-rich hydroxide is Co x M 1-x-t A t (OH) 2+δ , where 0.6 < x ≤ 1, 0 ≤ t ≤ 0.1, 0 ≤ δ ≤ 0.3, M is at least one of Al, Ni, Mn, Mg, Ti, and Zr; A is at least one of Mo, Cr, B, La, Y, Nb, and Er.
[0023] In a second aspect, the present application also provides a method for preparing the above cobalt-rich hydroxide, including:
[0024] Under the protection of an inert atmosphere, start stirring, add a cobalt-containing salt solution, a precipitant, and a complexing agent solution to a bottom liquid for coprecipitation reaction to obtain a hydroxide slurry; wash, dry, and pulverize the hydroxide slurry to obtain the cobalt-rich hydroxide;
[0025] Among them, the flow rate of adding the complexing agent solution is divided into a first step and a second step in sequence, and the flow rate of the complexing agent solution in the first step > the flow rate of the complexing agent solution in the second step.
[0026] In some embodiments, at least one of the following conditions is satisfied:
[0027] A. The total mass concentration of metal ions in the cobalt-containing salt solution is 90 g / L to 140 g / L;
[0028] B. The cobalt-containing salt solution further includes at least one of Al, Ni, Mn, Mg, Ti, Zr, Mo, Cr, B, La, Y, Nb, and Er;
[0029] C. The precipitant solution is a sodium hydroxide solution;
[0030] D. The mass concentration of the precipitant solution is 240 g / L to 440 g / L;
[0031] E. The complexing agent solution is ammonia water and / or ethylenediamine solution;
[0032] F. The mass concentration of the complexing agent solution is 10 g / L to 30 g / L;
[0033] G. The bottom liquid is a mixture of pure water, the precipitant solution, and the complexing agent solution, and the volume ratio of the water, the complexing agent solution, and the precipitant solution is V 水 : V 络合剂 : V沉淀剂 =(20~120):(0~2.5):1;
[0034] H. The volume of the bottom liquid is 20v% to 50v% of the volume of the reactor;
[0035] I. In the coprecipitation reaction, the flow rate of adding the cobalt-containing salt solution is 6% / h-30% / h of the volume of the reactor;
[0036] J. In the coprecipitation reaction, when the precipitant solution and the cobalt-containing salt solution are added, the mass ratio of the precipitant in the precipitant solution to the metal element in the cobalt-containing salt solution is (1.25-1.65):1;
[0037] K. The flow rate of the complexing agent solution in the first step is 2.5% / h-6.0% / h of the volume of the reactor, and the flow rate of the complexing agent solution in the second step is 0-1.5% / h of the volume of the reactor;
[0038] L. The time for adding the complexing agent solution in the first step and the second step is independently 0.2h-2.5h;
[0039] M. The stirring frequency is 40Hz-50Hz;
[0040] N. The temperature of the coprecipitation reaction is 30°C to 60°C;
[0041] O. The washing liquid used in the washing is pure water, and the washing temperature is 50°C to 75°C;
[0042] P. The drying temperature is 80°C to 110°C and the drying time is 8h to 15h;
[0043] Q. The pulverization is divided into the first pulverization and the second pulverization. The first pulverization is performed by using a disc nest mill and then passing through a 60-100 mesh sieve. The second pulverization is performed by using a jet mill. The feeding frequency of the second pulverization is 5Hz-8Hz.
[0044] In a third aspect, the present application provides a cobalt-coated positive electrode material, wherein the secondary particles of the cobalt-coated positive electrode material include a matrix and a coating layer, the matrix includes the positive electrode material, and the raw material of the coating layer includes the above-mentioned cobalt-rich hydroxide.
[0045] In a fourth aspect, the present application also provides a method for preparing the above-mentioned cobalt-coated positive electrode material, comprising: mixing the positive electrode material with the cobalt-rich hydroxide and then sintering to obtain the cobalt-coated positive electrode material.
[0046] In some embodiments, at least one of the following conditions is met:
[0047] A. The average particle size D50 of the cobalt-coated positive electrode material is 10 μm-15 μm;
[0048] B. The amount of the cobalt-rich hydroxide added is 0.01wt%-5wt% of the positive electrode material;
[0049] C. The mixing time is 30min to 60min;
[0050] D. The sintering temperature is 600°C to 900°C;
[0051] E. The sintering time is 5h to 12h.
[0052] In a fifth aspect, the present application also provides a lithium-ion battery, comprising the above-mentioned cobalt-coated positive electrode material.
[0053] Compared with the prior art, the beneficial effects of this application include:
[0054] The agglomeration coefficient of the cobalt-rich hydroxide provided in the present application is 1.1-2.0. The agglomeration coefficient is used to characterize the degree of agglomeration of the cobalt-rich hydroxide nanoparticles. The smaller the agglomeration coefficient, the better the dispersion of the particles. Good dispersion is conducive to more uniform coating of the particles on the surface of the positive electrode material. The surface of the secondary particles of the sintered positive electrode material is smooth, and the surface of the primary particles is smooth. After being prepared into a battery, it helps to isolate the positive electrode material from contact with the electrolyte, protect the positive electrode material from electrolyte corrosion, inhibit the generation of side reactions, and reduce the amount of residual alkali on the surface, thereby improving the surface stability of the positive electrode material and enhancing the electrochemical performance of the positive electrode material.
[0055] The preparation method of cobalt-rich hydroxide provided in the present application has good dispersibility and uniform particle size distribution by adjusting the flow rate of the added complexing agent solution. In addition, the preparation method of the present application does not require the addition of a dispersant, and the process is simple, environmentally friendly, and has low production costs.
[0056] The surface of the cobalt-coated positive electrode material provided in the present application is uniformly coated with the above-mentioned cobalt-rich hydroxide. The sintered coating layer helps to isolate the positive electrode material from contact with the electrolyte, protect the positive electrode material from electrolyte corrosion, inhibit the generation of side reactions, has low surface residual alkali, good surface stability, and good conductivity, and the corresponding electrochemical performance is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0058] Figure 1This is a surface SEM photograph of the cobalt-rich hydroxide of Example 1;
[0059] Figure 2 is the XRD pattern of the cobalt-rich hydroxide of Example 1;
[0060] Figure 3 This is a surface SEM photograph of the cobalt-rich hydroxide and cathode material mixture of Example 1 before sintering;
[0061] Figure 4 for Figure 3 A partial enlarged photo of
[0062] Figure 5 This is a surface SEM photograph of the cobalt-coated positive electrode material after sintering in Example 1;
[0063] Figure 6 This is a surface SEM photograph of the cobalt-rich hydroxide of Comparative Example 1;
[0064] Figure 7 is the XRD pattern of the cobalt-rich hydroxide of Comparative Example 1;
[0065] Figure 8 This is a surface SEM photograph of the cobalt-rich hydroxide and the positive electrode material of Comparative Example 1 before mixed sintering;
[0066] Fig. 9 for Figure 8 A partial enlarged photo of
[0067] Fig.10 This is a surface SEM photograph of the cobalt-coated positive electrode material after sintering in Comparative Example 1;
[0068] Fig.11 This is a surface SEM photograph of the cobalt-rich hydroxide of Comparative Example 2;
[0069] Fig.12 This is a surface SEM photograph of the cobalt-rich hydroxide of Comparative Example 3;
[0070] Fig.13 Surface SEM photos of the substrates used in Examples 1-12 and Comparative Examples 1-3;
[0071] Fig.14 for Fig.13 A partial enlarged photo of the . DETAILED DESCRIPTION
[0072] As used herein:
[0073] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0074] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0075] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0076] In these examples, parts and percentages are by mass unless otherwise indicated.
[0077] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0078] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0079] The present application provides a cobalt-rich hydroxide, and the agglomeration coefficient of the cobalt-rich hydroxide in,
[0080] d BET is the average particle size of the aggregates, calculated as d BET=6 / (ρ·BET),
[0081] ρ is the true density of cobalt-rich hydroxide, BET is the specific surface area of cobalt-rich hydroxide measured by BET method,
[0082] is the average crystal size of cobalt-rich hydroxide.
[0083] Optionally, the It is the average crystallite size of cobalt-rich hydroxide calculated by X-ray diffraction test using Cu-Kα rays.
[0084] The true density refers to the actual mass of a solid substance per unit volume in an absolutely dense state, that is, the density after removing the internal pores or gaps between particles;
[0085] The aggregates refer to larger particles that are agglomerated;
[0086] The crystal grains are basic microscopic structural units composed of atoms or molecules arranged in an orderly manner, and have a regular structure and specific crystallographic properties;
[0087] The average grain size refers to the average size of each surface of the grains inside the crystal, and is one of the important parameters for characterizing the microstructure of the material.
[0088] Optionally, the agglomeration coefficient of the cobalt-rich hydroxide provided in the present application may be, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any value between 1.1-2.0, 1.1-1.7;
[0089] Optionally, the agglomeration coefficient of the cobalt-rich hydroxide
[0090] For example, the molar ratio of Co:Ni:Mn in the cobalt-rich hydroxide in Example 1 is 75:15:10. It is assumed that the cobalt-rich hydroxide in Example 1 is composed of 75 mol% of cobalt hydroxide, 15 mol% of nickel hydroxide, and 10 mol% of manganese hydroxide. The calculation process of the agglomeration coefficient CF of the cobalt-rich hydroxide is:
[0091] ρ=75mol%×ρ Co(OH)2 +15mol%×ρ Ni(OH)2 +10mol%×ρ Mn(OH)2
[0092] =75mol%×3.60+15mol%×4.10+10mol%×3.26
[0093] =3.64g / cm 3 ;
[0094]
[0095] Among them, D (001) , D (001) , D (100) , D (101) , D (002) , D (102) , D (110) , D (003) , D (111) , D (200) , D (103) , D (201) , D (202) , D (112) The corresponding grain sizes are (001), (100), (101), (002), (102), (110), (003), (111), (200), (103), (201), (202), and (112) respectively;
[0096] In the X-ray diffraction of cobalt-rich hydroxide using Cu-Kα rays, the (001) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 18.5°-19.5°, the (100) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 31.8°-32.8°, the (101) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 37.2°-38.2°, the (002) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 37.9°-38.9°, the (102) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 50.7°-51.7°, the (110) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 57.2°-58.2°, and the (00 The (3) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 58.9°-59.9°, the (111) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 60.8°-61.8°, the (200) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 67.3°-68.3°, the (103) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 68.8°-69.8°, the (201) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 70.6°-71.6°, the (202) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 80.3°-81.3°, and the (112) crystal plane corresponds to a diffraction peak with a diffraction angle 2θ of 71.3°-72.3°.
[0097] The half-peak width FWHM(001) of the diffraction peak corresponding to the (001) crystal plane in the XRD spectrum of the positive electrode material precursor represents the width of the diffraction peak corresponding to the (001) crystal plane when the peak height is half, and the unit is degree (°). The grain size D of the (001) crystal plane (001)It refers to the grain size obtained by numerically fitting the diffraction peak corresponding to the (001) crystal plane, in nanometers (nm), which can be calculated by the Scherrer formula D=Kλ / (βcosθ), where K is the Scherrer constant, λ is the wavelength of the X-ray, β is the half-peak width of the diffraction peak corresponding to the (001) crystal plane, and θ is the diffraction angle of the (001) crystal plane.
[0098] Exemplarily, the grain size data of the positive electrode material precursor in Example 1 of the present invention can be obtained by refining the XRD data obtained by the test using the Japanese Rigaku XRD analysis software package and then calculating using the Scherrer formula; it can also be calculated directly by the Scherrer formula based on the XRD test data. In the above Scherrer formula, K=0.943 is selected, the wavelength of the ray λ is 0.15418nm, the double diffraction angle 2θ is 19.002°, and the half-peak width β of the diffraction peak corresponding to the (001) crystal plane is 0.269° (converted to radians [(β÷180)×π]), and the calculation process is:
[0099]
[0100] In the natural state, fine particles tend to aggregate together to form agglomerates. This spontaneous aggregation tendency will affect its dispersion performance, resulting in uneven coating and decreased sintering density. The aggregation coefficient is used to characterize the degree of agglomeration of cobalt-rich hydroxide particles. The closer the aggregation coefficient CF is to 1 (theoretically, there are no aggregates, and the theoretical value of CF is 1), the better the particle dispersion is, which is conducive to more uniform coating of particles on the surface of the positive electrode material, thereby effectively improving the coating uniformity.
[0101] The cobalt-rich hydroxide of the present application has a small agglomeration coefficient CF and can be evenly coated on the surface of the positive electrode material. The surface of the secondary particles of the sintered positive electrode material and the surface of the primary particles are smooth. After being prepared into a battery, the uniform coating layer helps to isolate the positive electrode material from the contact with the electrolyte, protect the positive electrode material from electrolyte corrosion, inhibit the generation of side reactions, and reduce the amount of residual alkali on the surface, thereby improving the surface stability of the cobalt-coated positive electrode material after sintering and enhancing its electrochemical performance after being prepared into a battery.
[0102] In some embodiments, the cobalt-rich hydroxide has a BET surface area of 30 m 2 / g-45m 2 / g, for example, 30m 2 / g, 31m 2 / g, 32m 2 / g, 33m 2 / g, 34m 2 / g, 35m 2 / g, 36m 2 / g, 37m 2 / g, 38m 2 / g, 39m 2 / g, 40m 2 / g, 41m 2 / g, 42m 2 / g, 43m 2 / g, 44m 2 / g, 45m 2 / g or 30m 2 / g-45m 2 Any value between / g.
[0103] The cobalt-rich hydroxide of the present application has a large specific surface area, which is beneficial to increasing the contact area with the positive electrode material during coating. During subsequent sintering, it can be better integrated into the surface of the secondary particles and the primary particles of the positive electrode material, thereby improving the smoothness of the surface of the cobalt-coated positive electrode material after sintering and improving the cycle performance of the prepared battery.
[0104] In some embodiments, the cobalt-rich hydroxide BET =6 / (ρ·BET)=34nm-65nm, for example, it can be 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 51nm, 52nm, 53nm, 54nm, 55nm, 56nm, 57nm, 58nm, 59nm, 60nm, 61nm, 62nm, 63nm, 64nm, 65nm or any value between 34nm and 65nm.
[0105] The cobalt-rich hydroxide in this application BET The smaller the size, the better the particles coated on the surface of the positive electrode material can be integrated into the surface of the primary particles of the secondary particles of the positive electrode material during subsequent sintering, thereby improving the smoothness of the surface of the cobalt-coated positive electrode material after sintering and improving the cycle performance of the prepared battery.
[0106] In some embodiments, the average crystal size of the cobalt-rich hydroxide is It can be 30nm-45nm, for example, it can be 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38,nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm or any value between 30nm and 45nm.
[0107] This application contains cobalt-rich hydroxide When it is within the above range, it is beneficial that during subsequent sintering, the particles coated on the surface of the positive electrode material can be better integrated into the surface of the primary particles of the secondary particles of the positive electrode material, thereby improving the smoothness of the surface of the cobalt-coated positive electrode material after sintering and improving the cycle performance of the prepared battery.
[0108] In some embodiments, the average crystal size of the cobalt-rich hydroxide is It is the average value of the grain sizes of the (001) crystal plane, (100) crystal plane, (101) crystal plane, (002) crystal plane, (102) crystal plane, (110) crystal plane, (003) crystal plane, (111) crystal plane, (200) crystal plane, (103) crystal plane, (201) crystal plane, (202) crystal plane, and (112) crystal plane.
[0109] There are two types of agglomeration states of particles: one is a hard agglomeration state where particles are combined with a strong binding force, such as secondary particles, tertiary particles, etc., which are difficult to break up using external forces such as vibration; the other is a soft agglomeration state where particles are loosely aggregated together, which can be easily broken up using external forces such as touch and vibration. In order to improve the dispersion performance of the material, the agglomeration state of the particles tends to be a soft agglomeration state. When testing the loose density AD of the sample, there is no need to oscillate repeatedly, and the sample has particles in a soft agglomeration state; when testing the vibration density TD of the sample, it will oscillate repeatedly, and the particles in the soft agglomeration state in the sample will be broken up, and only particles in a hard agglomeration state will exist. The ratio of the agglomeration state Hausner ratio = TD / AD can reflect the agglomeration state. When the agglomeration state Hausner ratio increases, it means that the particles are mainly soft agglomerates, with fewer hard agglomerates, and the particle dispersion performance is better.
[0110] In some embodiments, the agglomerated state Hausner ratio of the cobalt-rich hydroxide = TD / AD is 2.0-3.0, for example, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 or any value between 2.0 and 3.0.
[0111] Among them, the tap density TD of cobalt-rich hydroxide is 0.50 g / cm 3 -0.85g / cm 3 , for example, it can be 0.50 g / cm 3 , 0.51g / cm 3 , 0.52g / cm 3 , 0.53g / cm 3 , 0.54g / cm 3 , 0.55g / cm 3 , 0.56g / cm 3 , 0.57g / cm 3 、0.58g / cm 3、0.59g / cm 3 , 0.60g / cm 3 、0.61g / cm 3 , 0.62g / cm 3 , 0.63g / cm 3 , 0.64g / cm 3 , 0.65g / cm 3 , 0.66g / cm 3 , 0.67g / cm 3 , 0.68g / cm 3 , 0.69g / cm 3 、0.70g / cm 3 , 0.71g / cm 3 , 0.72g / cm 3 , 0.73g / cm 3 , 0.74g / cm 3 , 0.75g / cm 3 , 0.76g / cm 3 , 0.77g / cm 3 、0.78g / cm 3 , 0.79g / cm 3 , 0.80g / cm 3 、0.81g / cm 3 , 0.82g / cm 3 , 0.83g / cm 3 , 0.84g / cm 3 , 0.85g / cm 3 or 0.50g / cm 3 -0.85g / cm 3 Any value in between.
[0112] The bulk density AD of cobalt-rich hydroxide is 0.20 g / cm 3 -0.50g / cm 3 , for example, it can be 0.20 g / cm 3 , 0.21g / cm 3 , 0.22g / cm 3 , 0.23g / cm 3 , 0.24g / cm 3 , 0.25g / cm 3 , 0.26g / cm 3 , 0.27g / cm 3 , 0.28g / cm 3 , 0.29g / cm 3 , 0.30g / cm 3 , 0.31g / cm 3, 0.32g / cm 3 , 0.33g / cm 3 , 0.34g / cm 3 , 0.35g / cm 3 , 0.36g / cm 3 , 0.37g / cm 3 , 0.38g / cm 3 , 0.39g / cm 3 , 0.40g / cm 3 , 0.41g / cm 3 , 0.42g / cm 3 , 0.43g / cm 3 , 0.44g / cm 3 , 0.45g / cm 3 , 0.46g / cm 3 , 0.47g / cm 3 , 0.48g / cm 3 , 0.49g / cm 3 , 0.50g / cm 3 or 0.20g / cm 3 -0.50g / cm 3 Any value in between.
[0113] The cobalt-rich hydroxide of the present application has suitable TD, AD and a large Hausner ratio of agglomeration state. Suitable TD and AD can make the product not too fluffy and float on the surface of the mixture, affecting the coating effect; at the same time, the Hausner ratio can reflect the agglomeration state of the powder. When the ratio Hausner increases, it means that the prepared nanoparticles are mainly soft agglomerates with fewer hard agglomerates (soft agglomerates are easy to open when crushed), and the particle dispersion is relatively good; the nanoparticles have a suitable Hausner ratio, which means that they have good dispersibility. Particles with good dispersibility can be more evenly distributed in the positive electrode material, which can promote the filling performance of the positive electrode material and improve the cycle stability of the positive electrode material.
[0114] In some embodiments, in the X-ray diffraction pattern of the cobalt-rich hydroxide, the peak intensity of the diffraction peak corresponding to the (001) crystal plane is (001) The peak intensity of the diffraction peak corresponding to the (101) crystal plane is (101) The peak intensity ratio I (001) / I (101) It is 1.3-1.8, for example, it can be 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or any value between 1.3 and 1.8.
[0115] Peak intensity ratio of cobalt-rich hydroxide I (001) / I (101) Within this range, the corresponding coating performance is better.
[0116] In some embodiments, the average particle size D50 of the cobalt-rich hydroxide is 0.3 - 1.0 μm, and for example, it can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, or any value between 0.3 - 1.0 μm.
[0117] In some embodiments, the chemical formula of the cobalt-rich hydroxide is Co x M 1-x-t A t (OH) 2+δ , where 0.6 < x ≤ 1, 0 ≤ t ≤ 0.1, 0 ≤ δ ≤ 0.3, M is at least one of Al, Ni, Mn, Mg, Ti, and Zr; A is at least one of Mo, Cr, B, La, Y, Nb, and Er; for example, x can be 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.96, 0.99, or any value between 0.6 < x < 0.7, 0.7 ≤ x ≤ 0.8, 0.80 ≤ a ≤ 0.99, t can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or any value between 0 ≤ t ≤ 0.1, and δ can be 0, 0.1, 0.2, 0.3, or any value between 0 ≤ δ ≤ 0.3.
[0118] Cobalt hydroxide has good chemical stability, redox reaction activity, and electrochemical capacitance. In addition to being used as a precursor for preparing the cathode material LiCoO2, it can also be used as an additive for the cathode material. As an excellent additive, cobalt hydroxide can react with the residual alkali on the surface of the cathode material during the secondary sintering process of the material to form an active material coating layer, reduce interfacial side reactions, and improve the electrochemical performance of the battery.
[0119] The cobalt-rich hydroxide of the present application has specific doping elements. The introduction of doping elements can improve certain battery properties such as conductivity; in addition, the activity of cobalt hydroxide can be improved by doping, the specific surface area of the cobalt-rich hydroxide can be increased, and its loading capacity on the matrix material can be improved to enhance the coating effect, which is beneficial to the electrochemical performance of the cathode.
[0120] The present application also provides a preparation method of the above cobalt-rich hydroxide, including:
[0121] Under the protection of an inert atmosphere, start stirring, add a cobalt-containing salt solution, a precipitant solution, and a complexing agent solution to a bottom liquid for coprecipitation reaction to obtain a hydroxide slurry; wash, dry, and pulverize the hydroxide slurry to obtain cobalt-rich hydroxide;
[0122] The flow rate of adding the complexing agent solution is divided into the first step and the second step, and the flow rate of the complexing agent solution in the first step is greater than the flow rate of the complexing agent solution in the second step.
[0123] The preparation method of cobalt-rich hydroxide provided in the present application has good dispersibility and uniform particle size distribution by adjusting the flow rate of the added complexing agent solution. In addition, the preparation method of the present application does not require the addition of a dispersant, and the process is simple, environmentally friendly, and has low production costs.
[0124] In some embodiments, the total mass concentration of metal ions in the cobalt-containing salt solution is 90 g / L to 140 g / L, for example, it can be 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L or any value between 90 g / L and 140 g / L.
[0125] In some embodiments, the cobalt-containing salt solution further includes at least one of Al, Ni, Mn, Mg, Ti, Zr, Mo, Cr, B, La, Y, Nb, and Er.
[0126] In some embodiments, the precipitant solution is a sodium hydroxide solution; the mass concentration of the precipitant solution is 240g / L to 440g / L, for example, it can be 240g / L, 260g / L, 280g / L, 300g / L, 320g / L, 350g / L, 380g / L, 400g / L, 420g / L, 440g / L or any value between 240g / L and 440g / L.
[0127] In some embodiments, the complexing agent solution is aqueous ammonia and / or ethylenediamine solution; the mass concentration of the complexing agent solution is 10-30 g / L, for example, it can be 10 g / L, 7 g / L, 9 g / L, 10 g / L, 12 g / L, 15 g / L, 18 g / L, 20 g / L, 25 g / L, 30 g / L or any value between 10 g / L and 30 g / L.
[0128] In some embodiments, the base liquid is a mixture of pure water, the precipitant solution and the complexing agent solution, and the volume ratio of the water, the complexing agent solution and the precipitant solution is V 水 :V 络合剂 :V 沉淀剂 =(20~120):(0~2.5):1.
[0129] In some embodiments, the volume of the base liquid is 20v% to 50v% of the volume of the reactor, for example, it can be 20v%, 30v%, 40v%, 50v% or any value between 20v% and 50v%.
[0130] The volume of the base liquid is v% of the volume of the reactor, which refers to the ratio of the volume of the base liquid to the volume of the reactor. The volume ratio and content of water, complexing agent and precipitant in the base liquid can affect the size and quantity of primary particles generated at the beginning of the subsequent coprecipitation reaction.
[0131] In some embodiments, in the co-precipitation reaction, the flow rate of adding the cobalt-containing salt solution is 6% / h-30% / h of the volume of the reactor, for example, it can be 6% / h, 8% / h, 10% / h, 15% / h, 20% / h, 25% / h, 30% / h or any value between 6% / h and 30% / h.
[0132] In the coprecipitation reaction, the flow rate of the cobalt-containing salt solution can affect the size and number of primary particles generated.
[0133] In some embodiments, the mass ratio of the precipitant in the precipitant solution to the metal element in the cobalt-containing salt solution is (1.25-1.65):1, for example, it can be 1.25:1, 1.30:1, 1.35:1, 1.40:1, 1.45:1, 1.50:1, 1.55:1, 1.60:1, 1.65:1 or any ratio between (1.25-1.65):1.
[0134] The preparation method of cobalt-rich hydroxide provided in the present application controls the supersaturation of the reaction system by reasonably and effectively matching the amount of base liquid added, temperature and mass ratio (the ratio of the mass of the precipitant in the precipitant solution to the mass of the metal element in the cobalt-containing salt solution), so that the particles are not easy to agglomerate during the reaction process, which is convenient for subsequent post-processing operations. The prepared cobalt-rich hydroxide product has good dispersibility and uniform particle size distribution. In addition, the preparation method of the present application does not require the addition of a dispersant, and the process is simple, environmentally friendly, and has low production costs.
[0135] In some embodiments, the flow rate of the complexing agent solution in the first step is 2.5% / h-6.0% / h of the volume of the reactor, for example, it can be 2.5% / h, 3.0% / h, 3.5% / h, 4.0% / h, 4.5% / h, 5.0% / h, 5.5% / h, 6.0% / h or any value between 2.5% / h and 6.0% / h; the flow rate of the complexing agent solution in the second step is 0-1.5% / h of the volume of the reactor, for example, it can be 0 (no complexing agent is added), 0.5% / h, 1.0% / h, 1.5% / h or any value between 0-1.5% / h.
[0136] In some embodiments, the time for adding the complexing agent solution in the first step and the second step is independently 0.2h-2.5h; for example, it can be 0.2h, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h or any value between 0.2h-2.5h.
[0137] The flow rate of the complexing agent is divided into the first step and the second step. In the first step, the solid content is low at the initial stage of the coprecipitation reaction, and the generated fine crystal nuclei are easy to agglomerate. By introducing the complexing agent solution, the crystal nucleus generation rate can be controlled, which is beneficial to inhibiting the aggregation and agglomeration of the initial particles, and obtaining the initial particles with small size and dispersion. If the amount of complexing agent added in the first step is too much, the supersaturation of the system will be too low, resulting in the initial particles being too large in size. If the amount of complexing agent added in the first step is too low, the initial stable reaction system cannot be formed, which will lead to the aggregation and agglomeration tendency of the particles not being fully inhibited, the initial particles are not dispersed well, and the subsequent particle growth is affected. In the second step, based on the first step, the solid content of the reaction system increases, and the reaction system tends to be basically stable. At this time, it is necessary to reduce or stop the use of the complexing agent, and make full use of the residual ammonium ions in the first step or the newly introduced small amount of ammonium ions to maintain the stability of the system, control the particle growth rate and maintain the dispersion of the particles in the reaction system, which is beneficial to obtain flaky particles with good size uniformity and dispersion. If the amount of complexing agent added in the second step is too much, the initial particles will grow too fast, and the particles will easily grow in an interlaced and stacked manner, which will eventually lead to a large particle size.
[0138] In some embodiments, the stirring frequency is 40 Hz-50 Hz, for example, 40 Hz, 42 Hz, 44 Hz, 46 Hz, 48 Hz, 50 Hz or any value between 40 Hz and 50 Hz;
[0139] The stirring frequency is the number of times the stirrer rotates per second, which is closely related to the speed (number of revolutions per minute). The specific relationship is: the stirring frequency is equal to the stirring speed divided by 60. A faster stirring speed is conducive to fully dispersing the slurry in the kettle, avoiding agglomeration growth, and improving the dispersion of the material.
[0140] In some embodiments, the coprecipitation reaction temperature is 30°C to 60°C, for example, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or any value between 30°C and 60°C.
[0141] Appropriate temperature selection can control the reaction rate of the coprecipitation reaction to control the crystallinity of the particles, and then regulate the particle size and particle surface energy, reducing the degree of particle agglomeration; too low a temperature will produce particles with low crystallinity and high particle surface energy, and the particles are relatively easy to agglomerate; while too high a temperature will cause violent collisions between particles in the coprecipitation reaction, and they are easy to agglomerate into secondary agglomerate balls, resulting in poor dispersion of the system.
[0142] In some embodiments, the washing liquid used for washing is pure water, and the washing temperature is 50°C to 75°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or any value between 50°C and 75°C.
[0143] In some embodiments, the drying temperature is 80°C to 110°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C or any value between 80°C and 110°C, and the time is 8h to 15h, for example, it can be 8h, 10h, 12h, 15h or any value between 8h and 15h.
[0144] In some embodiments, the pulverization is divided into a first pulverization and a second pulverization. The first pulverization is performed by using a disc mill and then passing through a 60-100 mesh sieve. The second pulverization is performed by using a jet mill. The feeding frequency of the second pulverization is 5Hz-8Hz.
[0145] Through secondary crushing, the particles with larger particle size and agglomerated adhesion are fully broken, and the material can be ground more fully to ensure the uniform distribution of particle size, further improving the dispersion of particles. Specifically, the first crushing uses a disc nest mill to coarsely break, deagglomerate and screen the dried agglomerated materials (due to the small particle size of the primary particles, they will agglomerate after drying) to obtain the primary crushed materials; the second crushing uses a jet mill to grade and screen the primary crushed materials, further break up some of the agglomerated and adhered particles, and refine the particle size, and finally obtain a finished product material with no agglomeration and adhesion, uniform particle size and good dispersion.
[0146] The present application also provides a cobalt-coated positive electrode material, the raw materials of which include the above-mentioned cobalt-rich hydroxide;
[0147] Optionally, the secondary particles of the cobalt-coated positive electrode material include a matrix and a coating layer, the matrix includes the positive electrode material, the raw material of the coating layer includes the above-mentioned cobalt-rich hydroxide, and the secondary particles are formed by stacking primary particles.
[0148] The surface of the cobalt-coated positive electrode material provided in the present application is coated with the above-mentioned cobalt-rich hydroxide, and the coating layer is lithium cobaltate or doped lithium cobaltate. The coating layer helps to isolate the positive electrode material from contact with the electrolyte, protect the positive electrode material from electrolyte corrosion, inhibit the generation of side reactions, have low surface residual alkali, good surface stability, and correspondingly improve electrochemical performance.
[0149] Among them, the positive electrode materials include lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, binary material lithium nickel cobalt oxide, binary material lithium nickel manganese oxide, ternary material lithium nickel cobalt manganese oxide, ternary material lithium nickel cobalt aluminum oxide, lithium-rich manganese-based positive electrode materials and any one of the modified dopants of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, binary material lithium nickel cobalt oxide, binary material lithium nickel manganese oxide, ternary material lithium nickel cobalt manganese oxide, ternary material lithium nickel cobalt aluminum oxide and lithium-rich manganese-based positive electrode materials.
[0150] The present application also provides a method for preparing the cobalt-coated positive electrode material according to the above, comprising: mixing the positive electrode material with a cobalt-rich hydroxide and then sintering to obtain the cobalt-coated positive electrode material.
[0151] In some embodiments, the average particle size D50 of the cobalt-coated positive electrode material is 10 μm-15 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any value between 10 μm and 15 μm.
[0152] In some embodiments, the amount of cobalt-rich hydroxide added is 0.01wt%-5wt% of the positive electrode material, for example, it can be 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or any value between 0.01wt%-5wt%.
[0153] In some embodiments, the mixing time is 30 min to 60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min or any value between 30 min and 60 min.
[0154] In some embodiments, the sintering temperature is 600°C to 900°C, for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C or any value between 600°C and 900°C; the sintering time is 5h to 12h, for example, it can be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value between 5h and 12h.
[0155] The present application also provides a lithium-ion battery, comprising the above-mentioned cobalt-coated positive electrode material.
[0156] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0157] Example 1
[0158] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2 comprises the following steps:
[0159] ① Raw material preparation: Weigh battery-grade cobalt sulfate, nickel sulfate and manganese sulfate, add pure water to prepare a cobalt-containing salt solution with a total metal ion mass concentration of 120 g / L, wherein the molar ratio of cobalt, nickel and manganese is 75:15:10; prepare a sodium hydroxide solution with a mass concentration of 320 g / L; prepare ammonia water with a mass concentration of 15 g / L.
[0160] ② Coprecipitation reaction
[0161] Preparation of base liquid: Start stirring under N2 protection at a frequency of 45 Hz, and add V 水 :V 络合剂 :V 沉淀剂 =100:1:1 pure water, sodium hydroxide solution and ammonia water are prepared into a base liquid, and the volume of the base liquid is 30v% of the volume of the reactor;
[0162] Step 1: Raise the temperature to 45°C, add the cobalt-containing salt solution, sodium hydroxide solution and ammonia water into the reactor in parallel for coprecipitation reaction, wherein the flow rate of the cobalt-containing salt solution is 18% / h of the volume of the reactor, the mass ratio of the sodium hydroxide in the added sodium hydroxide solution to the mass ratio of the metal element in the cobalt-containing salt solution is 1.42:1, and the flow rate of the ammonia water is 3.2% / h of the volume of the reactor for 1 hour;
[0163] Step 2: The flow rate of the ammonia water is adjusted to 0.5% / h of the volume of the reactor, and the reaction is continued for 0.5h, then the reaction is stopped and then aged to obtain a hydroxide slurry.
[0164] ③ Washing and drying: Wash the hydroxide slurry obtained in step ② with pure water for 3 times at a temperature of 60°C; dry the washed hydroxide slurry in a vacuum drying oven at 90°C for 12 hours to obtain a dried material.
[0165] ④ Crushing
[0166] First crushing: the dried material obtained in step ③ is crushed by a disc nest mill and then passed through an 80-mesh sieve, the sieved material is returned to the crusher, and the sieved material is collected;
[0167] Second crushing: The undersize material is crushed using a jet mill with a feed frequency of 6 Hz to obtain cobalt-rich hydroxide.
[0168] ⑤ Coating and sintering: Cobalt-rich hydroxide and ternary positive electrode material (molecular formula: LiNi 0.925 Co 0.05 Mn 0.025O2) is mixed for 40 minutes, the amount of cobalt-rich hydroxide added is 1wt% of the ternary positive electrode material, and then the mixed material is placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min and sintered for 8h. After natural cooling, the sintered material is crushed and sieved to obtain a cobalt-coated ternary positive electrode material.
[0169] Example 2
[0170] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0171] ② Coprecipitation reaction
[0172] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =80:1:1, the volume of the bottom liquid is 28v% of the volume of the reactor;
[0173] Step 1: Heat to 50°C, the flow rate of the cobalt-containing salt solution is 15% / h of the reactor volume, the mass ratio of the sodium hydroxide in the added sodium hydroxide solution to the metal element in the cobalt-containing salt solution is 1.50:1, and the flow rate of ammonia water is adjusted to 0.5% / h of the reactor volume for 1.5h;
[0174] The other reaction conditions are the same as those in Example 1, and the same applies below.
[0175] Example 3
[0176] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0177] ② Coprecipitation reaction
[0178] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =80:1:1; the volume of the bottom liquid is 28v% of the volume of the reactor;
[0179] Step 1: The temperature is raised to 50° C. and the flow rate of the cobalt-containing salt solution is 30% / h of the volume of the reactor.
[0180] Example 4
[0181] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0182] ② Coprecipitation reaction
[0183] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =40:1.5:1;
[0184] Step 1: The temperature is raised to 40°C, the flow rate of the cobalt-containing salt solution is 16% / h of the volume of the reactor, and the flow rate of the ammonia water is 2.8% / h of the volume of the reactor;
[0185] Step 2: The flow rate of ammonia water was adjusted to 0.5% / h of the reactor volume and the reaction was continued for 1 h.
[0186] Example 5
[0187] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0188] ② Coprecipitation reaction
[0189] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =40:1.5:1; the volume of the bottom liquid is 20v% of the volume of the reactor;
[0190] Step 1: Heat to 30°C, flow rate of cobalt-containing salt solution is 15% / h of reactor volume, flow rate of ammonia water is 2.8% / h of reactor volume, and react for 1.5h;
[0191] Step 2: The flow rate of ammonia water was adjusted to 0.5% / h of the reactor volume and the reaction was continued for 1 h.
[0192] Example 6
[0193] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0194] ② Coprecipitation reaction
[0195] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =60:1.5:1, the volume of the bottom liquid is 25v% of the volume of the reactor;
[0196] Step 1: The flow rate of the cobalt-containing salt solution is 25% / h of the volume of the reactor, and the flow rate of the ammonia water is 2.8% / h of the volume of the reactor; the reaction time is 0.75h;
[0197] Step 2: Stop adding ammonia water, continue the reaction for 0.75h, then stop the reaction, and then perform aging treatment to obtain hydroxide slurry.
[0198] Example 7
[0199] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0200] ② Coprecipitation reaction
[0201] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =60:1.5:1, the volume of the bottom liquid is 20v% of the volume of the reactor;
[0202] Step 1: The temperature is raised to 55°C, the flow rate of the cobalt-containing salt solution is 25% / h of the volume of the reactor, and the flow rate of the ammonia water is 4.0% / h of the volume of the reactor; the reaction time is 0.75h;
[0203] Step 2: The flow rate of the ammonia water is adjusted to 1.0% / h of the volume of the reactor, and the reaction is continued for 1.25 hours, then the reaction is stopped and then aged to obtain a hydroxide slurry.
[0204] Example 8
[0205] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0206] ② Coprecipitation reaction
[0207] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =120:2:1;
[0208] Step 1: Heat to 35°C, the flow rate of the cobalt-containing salt solution is 8% / h of the reactor volume, the mass ratio of the sodium hydroxide in the added sodium hydroxide solution to the metal element in the cobalt-containing salt solution is 1.35:1, the flow rate of ammonia water is 3.2% / h of the reactor volume, and the reaction is carried out for 2.0h;
[0209] Step 2: The flow rate of the ammonia water is adjusted to 0.25% / h of the volume of the reactor, and the reaction is continued for 2 hours, then the reaction is stopped and an aging treatment is performed to obtain a hydroxide slurry.
[0210] Example 9
[0211] This embodiment provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0212] ② Coprecipitation reaction
[0213] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =100:1:1;
[0214] Step 1: The flow rate of the cobalt-containing salt solution is 15% / h of the reactor volume, and the flow rate of the ammonia water is 3.2% / h of the reactor volume for 1 hour;
[0215] Step 2: Stop adding ammonia water, continue the reaction for 1 hour, then stop the reaction, and then perform aging treatment to obtain hydroxide slurry.
[0216] Example 10
[0217] This embodiment provides a method for preparing cobalt-rich hydroxide Co(OH)2, and the reaction conditions different from those in Example 1 are:
[0218] ① Raw material preparation: Weigh battery-grade cobalt sulfate and add pure water to prepare a cobalt-containing salt solution with a total metal ion concentration of 120 g / L;
[0219] ② Coprecipitation reaction
[0220] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =40:1.5:1, the volume of the bottom liquid is 50v% of the volume of the reactor;
[0221] Step 1: The temperature is raised to 40°C, the flow rate of the cobalt-containing salt solution is 16% / h of the reactor volume, the mass ratio of the sodium hydroxide in the added sodium hydroxide solution to the metal element in the cobalt-containing salt solution is 1.55:1, the flow rate of ammonia water is 4.5% / h of the reactor volume, and the reaction is carried out for 1 hour;
[0222] Step 2: The flow rate of the ammonia water is adjusted to 1.5% / h of the volume of the reactor, and the reaction is continued for 1 hour, then the reaction is stopped and then aged to obtain a hydroxide slurry.
[0223] Embodiment 11
[0224] This embodiment provides a cobalt-rich hydroxide Co 88 Ni 12 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0225] ① Raw material preparation: Weigh battery-grade cobalt sulfate and nickel sulfate, add pure water to prepare a cobalt-containing salt solution with a total metal ion mass concentration of 120 g / L, wherein the molar ratio of cobalt to nickel is 88:12.
[0226] ② Coprecipitation reaction
[0227] Preparation of base liquid: stirring frequency is 40Hz, V 水 :V 络合剂 :V 沉淀剂 =20:2.5:1, the volume of the bottom liquid is 35v% of the volume of the reactor;
[0228] Step 1: The flow rate of the cobalt-containing salt solution is 20% / h of the reactor volume, the mass ratio of the sodium hydroxide in the added sodium hydroxide solution to the metal element in the cobalt-containing salt solution is 1.48:1, the flow rate of the ammonia water is 4.8% / h of the reactor volume, and the reaction is carried out for 0.5h;
[0229] Step 2: The flow rate of the ammonia water is adjusted to 0.5% / h of the volume of the reactor, and the reaction is continued for 0.5h, then the reaction is stopped and then aged to obtain a hydroxide slurry.
[0230] ③Washing and drying: The drying temperature is 100℃.
[0231] ④ Crushing
[0232] The feeding frequency of the jet mill used for the second crushing was 10 Hz.
[0233] ⑤ Coating and sintering: The amount of cobalt-rich hydroxide added is 1.5wt% of the ternary positive electrode material, and the temperature is raised to 700°C at a heating rate of 5°C / min and sintered for 6h.
[0234] Example 12
[0235] This embodiment provides a cobalt-rich hydroxide Co 95 Mg2Zr3(OH) 2.06 The preparation method has the following reaction conditions different from those in Example 1:
[0236] ① Raw material preparation: Weigh battery-grade cobalt sulfate, magnesium sulfate and zirconium sulfate, add pure water to prepare a cobalt-containing salt solution with a total metal ion mass concentration of 120 g / L, wherein the molar ratio of cobalt to nickel is 88:12.
[0237] ② Coprecipitation reaction
[0238] Base liquid preparation: stirring frequency is 50Hz, V 水 :V 络合剂 :V 沉淀剂 =20:2.5:1, the volume of the bottom liquid is 35v% of the volume of the reactor;
[0239] Step 1: Raise the temperature to 40°C, add a sodium hydroxide solution with a mass ratio of sodium hydroxide to the metal element in the cobalt-containing salt solution of 1.52:1, and ammonia water at a flow rate of 5.5% of the reactor volume / h for 1 hour;
[0240] ⑤ Coating and sintering: The amount of cobalt-rich hydroxide added is 2 wt% of the ternary positive electrode material, and the temperature is raised to 700°C at a heating rate of 5°C / min and sintered for 6 hours.
[0241] Comparative Example 1
[0242] This comparative example provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0243] ② Coprecipitation reaction
[0244] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =100:1:1, the volume of the bottom liquid is 28v% of the volume of the reactor;
[0245] Step 1: Heat to 50°C, the flow rate of the cobalt-containing salt solution is 45% / h of the reactor volume, the mass ratio of the sodium hydroxide in the added sodium hydroxide solution to the metal element in the cobalt-containing salt solution is 1.50:1, the flow rate of ammonia water is 1.8% / h of the reactor volume, and the reaction is carried out for 0.5h.
[0246] Comparative Example 2
[0247] This comparative example provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0248] ② Coprecipitation reaction
[0249] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =50:1:1;
[0250] Step 1: Heat to 25°C, add sodium hydroxide solution with a mass ratio of sodium hydroxide to metal elements in the cobalt-containing salt solution of 1.38:1, and flow rate of ammonia water is 1.8% / h of the reactor volume for 1 hour;
[0251] Step 2: The flow rate of the ammonia water is adjusted to 2% / h of the volume of the reactor, and the reaction is continued for 0.5h, then the reaction is stopped and then aged to obtain a hydroxide slurry.
[0252] ④ Crushing
[0253] First crushing: crush with disc nest mill and pass through 50 mesh sieve;
[0254] Second crushing: The feed frequency of the jet mill is 4 Hz.
[0255] Comparative Example 3
[0256] This comparative example provides a cobalt-rich hydroxide Co 75 Ni 10 Mn 15 The preparation method of (OH)2, the reaction conditions different from those in Example 1 are:
[0257] ② Coprecipitation reaction
[0258] Primer preparation: V in the primer 水 :V 络合剂 :V 沉淀剂 =50:1:1, the volume of the bottom liquid is 20v% of the volume of the reactor;
[0259] Step 1: The mass ratio of the sodium hydroxide in the added sodium hydroxide solution to the metal element in the cobalt-containing salt solution is 1.85:1, and no ammonia water is added to react for 1 hour;
[0260] Step 2: without adding ammonia water, continue the reaction for 1 hour, stop the reaction, and then perform aging treatment to obtain hydroxide slurry.
[0261] ④ Crushing
[0262] Second crushing: The feed frequency of the jet mill is 4 Hz.
[0263] Blank example
[0264] The ternary positive electrode material without the coating of cobalt-rich hydroxide used in Examples 1-12 and Comparative Examples 1-3 has a particle size D50 of 13 μm and a molecular formula of LiNi 0.925 Co 0.05 Mn 0.025 O2 (see the preparation method and subsequent sintering method of Example 1 of CN118108267A).
[0265] Test Example 1
[0266] The positive electrode material precursor prepared in the above example was tested for physical and chemical data, specifically:
[0267] The cobalt-rich hydroxides obtained in Examples 1 to 12 and Comparative Examples 1 to 3 were tested for physical and chemical properties, and the testing methods were as follows:
[0268] XRD data: measured by X-ray diffractometer, XRD test conditions are Cu target, wavelength 0.15418nm, voltage 40Kv, current 40mA; scanning angle 10~85°, step angle 0.013°, step time 0.2s.
[0269] Average particle size of secondary particles (D50): measured by laser particle size tester (instrument model: Mastersizer 3000), with reference to the national standard "GB / T 19077-2016 Particle size analysis laser diffraction method";
[0270] Specific surface area (BET method): measured by a fully automatic nitrogen adsorption specific surface area analyzer (instrument model: BELPREP-VACII / BELSORP-MINI-X), referring to the national standard "GB / T 19587-2017 Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method";
[0271] Tap density (TD): measured by a powder tap density tester (model: Dandong Better BT-302), with reference to the national standard "GB / T 5162-2021 Determination of tap density of metal powders";
[0272] Bulk density (AD): measured by bulk density tester (instrument model: Dandong Better BT-101), referring to the national standard "GB / T 1479.3-2017 Determination of bulk density of metal powder";
[0273] Contents of nickel, cobalt, manganese, etc.: Determined by inductively coupled plasma mass spectrometry (instrument model: Agilent7850ICP-MS), referring to the national standard "GB / T 8647.11-2019 Nickel Chemical Analysis Method Part 11_Determination of Magnesium, Aluminum, Manganese, Cobalt, Copper, Zinc, Cadmium, Tin, Antimony, Lead, Bismuth Content Inductively Coupled Plasma Mass Spectrometry" to determine the content of Li2CO3:
[0274] The present invention exemplarily provides SEM photos of the surface of cobalt-rich hydroxide prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively. Figure 1 , Figure 6 , Fig.11 and Fig.12 .
[0275] from Figure 1 It can be seen that the cobalt-rich hydroxide prepared in Example 1 is flaky particles with a relatively uniform particle size and good particle dispersibility, and no large agglomerated particles are formed (ie, the agglomeration coefficient CF is small).
[0276] from Figure 6 It can be seen that the cobalt-rich hydroxide prepared in Comparative Example 1 is flaky particles, and the particle dispersibility is poor, and large agglomerated particles have been formed (ie, the agglomeration coefficient CF is too large).
[0277] from Fig.11 It can be seen that the cobalt-rich hydroxide prepared in Comparative Example 2 is flaky particles with uneven particle size, a large number of large flaky particles, and poor particle dispersibility, and has formed large agglomerated particles (i.e., the agglomeration coefficient CF is too large).
[0278] from Fig.12 It can be seen that the cobalt-rich hydroxide prepared in Comparative Example 3 is flaky particles, and the particle dispersibility is poor, and a plurality of relatively large agglomerated particles have been formed (ie, the agglomeration coefficient CF is too large).
[0279] The present invention exemplarily provides XRD patterns of the cobalt-rich hydroxides prepared in Example 1 and Comparative Example 1; see Figure 2 and Figure 7 .pass Figure 2 , Figure 7 The grain size, peak intensity ratio, etc. corresponding to each crystal plane of the positive electrode material precursor obtained in Example 1 and Comparative Example 1 can be obtained by combining with professional software calculations.
[0280] The present invention exemplarily provides a surface SEM photo of an uncoated positive electrode material (see Fig.13 and Fig.14 ), and the surface SEM photos of the positive electrode materials before and after sintering of the cobalt-rich hydroxides of Example 1 and Comparative Example 1 (see Figure 3 , Figure 4 , Figure 5 , Figure 8 , Fig. 9 , Fig.10 ).
[0281] Fig.14 for Fig.13 A partial enlarged photo of Fig.13 , Fig.14 It can be seen that the surface of the primary particles of the uncoated secondary particles of the ternary positive electrode material is smooth, with only a very small number of fine particles attached to it.
[0282] Figure 4 for Figure 3 A partial enlarged photo of Figure 3 , Figure 4It can be seen from the figure that a large number of fine particles are attached to the surface of the secondary particles of the ternary positive electrode material of the cobalt-rich hydroxide coated in Example 1 before sintering, and a large number of fine particles are evenly dispersed.
[0283] from Figure 5 It can be seen that the surface of the secondary particles of the ternary positive electrode material coated with the cobalt-rich hydroxide of Example 1 after sintering is smooth, with a small amount of fine particles attached, and the particle size of the fine particles tends to increase compared with before sintering.
[0284] Fig. 9 for Figure 8 A partial enlarged photo of Figure 8 , Fig. 9 It can be seen that: a large number of agglomerated fine particles are attached to the surface of some surfaces of the secondary particles of the ternary positive electrode material of the cobalt-rich hydroxide before sintering of the coating comparison example 1, while fine particles are not attached to the surface of some surfaces of the primary particles, and the coating is uneven.
[0285] from Fig.10 It can be seen that: after the sintering of the cobalt-rich hydroxide in the coating comparison example 1, a large number of small particles agglomerated together are attached to the surface of some surfaces of the primary particles of the secondary particles, and small particles are not attached to the surface of some surfaces of the primary particles, the coating is uneven, and the particle size of the small particles tends to increase compared with before sintering.
[0286] Table 1 Physical and chemical properties of cobalt-rich hydroxides obtained in various embodiments and comparative examples
[0287]
[0288] Note: The positive electrode material D50 is the average particle size D50 of the ternary positive electrode material coated with the cobalt-rich hydroxide of the corresponding embodiment or comparative example after sintering.
[0289] Table 2 Physical and chemical properties of cobalt-rich hydroxides obtained in various embodiments and comparative examples
[0290]
[0291]
[0292] Test Example 2
[0293] The positive electrode materials of the above-mentioned embodiments, comparative examples and blank examples were stirred and mixed with the conductive agent super p and the binder PVDF in a mass ratio of 8:1:1, and the slurry was evenly coated on the aluminum foil using a coating machine, and then dried, rolled and punched to prepare the positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1 mol / L LiPF6 / EMC:DMC:EC (volume ratio 1:1:1). The battery shell, positive and negative electrode sheets, diaphragms, shrapnel, and gaskets were assembled into button batteries in a vacuum glove box. The electrochemical performance test was carried out at 1C using a blue electric test system, and the test conditions were 3.0-4.3V, 25°C, and 1C=210mAh / g. The residual alkali Li2CO3 on the surface of the positive electrode material after coating and sintering was tested by potentiometric titration, referring to the national standard "GB / T 41704-2022 Lithium Ion Battery Positive Electrode Material Detection Method Determination of Magnetic Foreign Matter Content and Residual Alkali Content". The battery performance of each embodiment and comparative example is shown in Table 3.
[0294] Table 3 Battery performance of each embodiment and comparative example
[0295]
[0296] Compared with the blank example, the agglomeration coefficient of the cobalt-rich hydroxide provided in Examples 1-12 of the present invention is 1.1-2.0, the agglomeration coefficient is small, and the dispersion of the particles is good, which is conducive to more uniform coating of the particles on the surface of the positive electrode material. The surface residual alkali (Li2CO3 content) of the positive electrode material after coating and sintering is low, and after being prepared into a battery, it has a higher cycle capacity retention rate of 50 cycles at 1C.
[0297] Compared with Example 1, the cobalt-rich hydroxide-coated positive electrode materials of Comparative Examples 1-3 have higher residual alkali on the surface after sintering, and the prepared batteries show poor capacity retention rate after 50 cycles at 1C. It is speculated that the possible reason is that the agglomeration coefficient CF of the cobalt-rich hydroxide is too large, the dispersion performance is poor, and the coating on the surface of the positive electrode material is uneven, which affects the surface smoothness of the primary particles of the surface of the positive electrode material after sintering.
[0298] Among them, Examples 1-3 are nickel- and manganese-doped cobalt-rich hydroxides. After the positive electrode materials are coated and sintered, the residual alkali on the surface is low. The prepared batteries show a high 50-cycle capacity retention rate at 1C. It is speculated that the possible reason is that the agglomeration coefficient CF is small and the coating uniformity is good. Compared with Example 1, the batteries prepared by sintering the positive electrode materials coated with nickel- and manganese-doped cobalt-rich hydroxides in Examples 4-5 show a slightly poor 50-cycle capacity retention rate at 1C. It is speculated that the average grain size The surface residual alkali of the nickel- and manganese-doped cobalt-rich hydroxide-coated positive electrode material of Example 6-7 after sintering is slightly higher, and the first discharge capacity at 1C is slightly worse after being prepared into a battery. It is speculated that the possible reason is dBET The surface residual alkali of the cobalt-rich hydroxide-coated positive electrode material doped with nickel and manganese in Example 8 after sintering is slightly higher, and the first discharge capacity at 1C after being prepared into a battery is slightly worse. It is speculated that the possible reason is that the Hausner ratio is too large, and it is not easy to mix evenly with the positive electrode material during mixing; the surface residual alkali of the cobalt-rich hydroxide-coated positive electrode material doped with nickel and manganese in Example 9 after sintering is slightly higher, and the first discharge capacity at 1C after being prepared into a battery is slightly worse. It is speculated that the possible reason is that the Hausner ratio is too small, the hard agglomeration is slightly more, and the particle dispersion is slightly worse; Example 10 is a slightly higher surface residual alkali of the undoped nickel and manganese cobalt-rich hydroxide-coated positive electrode material after sintering, and the first discharge capacity at 1C after being prepared into a battery is slightly worse. It is speculated that the possible reason is that the TD and AD of the undoped cobalt-rich hydroxide are too small, the product is fluffy, the sample mixing and coating uniformity is slightly worse, and the BET is too small, d BET Examples 11-12 are cobalt-rich hydroxides with different cobalt contents (cobalt molar contents are 88 mol% and 95 mol% respectively) and different doping. The corresponding electrochemical performance of the battery prepared after coating and sintering is good. It is speculated that the possible reason is that the agglomeration coefficient CF is too small (1.1-2.0) and is also applicable to different cobalt-rich products and various doping situations.
[0299] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A cobalt-rich hydroxide, characterized in that The agglomeration coefficient of the cobalt-rich hydroxide in, the BET =6 / (ρ·BET), ρ is the true density of the cobalt-rich hydroxide, BET is the specific surface area of the cobalt-rich hydroxide, is the average grain size of the cobalt-rich hydroxide.
2. The cobalt-rich hydroxide according to claim 1, characterized in that The cobalt-rich hydroxide satisfies at least one of the following conditions: A. Agglomeration coefficient of the cobalt-rich hydroxide B. The specific surface area of the cobalt-rich hydroxide is 30 m 2 / g-45m 2 / g; C. The cobalt-rich hydroxide BET =6 / (ρ·BET)=34nm-65nm; D. Average grain size of the cobalt-rich hydroxide 30nm-45nm; E. Average grain size of the cobalt-rich hydroxide is the average grain size on the (001) crystal plane, (100) crystal plane, (101) crystal plane, (002) crystal plane, (102) crystal plane, (110) crystal plane, (003) crystal plane, (111) crystal plane, (200) crystal plane, (103) crystal plane, (201) crystal plane, (202) crystal plane, and (112) crystal plane.
3. The cobalt-rich hydroxide according to claim 1 or 2, characterized in that The agglomeration state Hausner ratio of the cobalt-rich hydroxide is TD / AD of 2.0-3.0, wherein The tap density TD of the cobalt-rich hydroxide is 0.50 g / cm 3 -0.85g / cm 3 , The bulk density AD of the cobalt-rich hydroxide is 0.20 g / cm 3 -0.50g / cm 3 .
4. The cobalt-rich hydroxide according to claim 1, characterized in that The cobalt-rich hydroxide satisfies at least one of the following conditions: A. In the X-ray diffraction pattern of the cobalt-rich hydroxide, the peak intensity I of the diffraction peak corresponding to the (001) crystal plane is (001) The peak intensity I of the diffraction peak corresponding to the (101) crystal plane is (101) The peak intensity ratio I (001) / I (101) 1.3-1.8; B. the average particle size D50 of the cobalt-rich hydroxide is 0.3-1.0 μm; C. The chemical formula of the cobalt-rich hydroxide is Co x M 1-x-t A t (OH) 2+δ , where 0.6 < x ≤ 1, 0 ≤ t ≤ 0.1, 0 ≤ δ ≤ 0.3, M is at least one of Al, Ni, Mn, Mg, Ti, and Zr; A is at least one of Mo, Cr, B, La, Y, Nb, and Er.
5. A method for preparing the cobalt-rich hydroxide according to any one of claims 1 to 4, characterized in that: include: Under the protection of an inert atmosphere, stirring is started, and a cobalt-containing salt solution, a precipitant solution, and a complexing agent solution are added to the bottom liquid for coprecipitation reaction to obtain a hydroxide slurry; the hydroxide slurry is washed, dried, and crushed to obtain the cobalt-rich hydroxide; The flow rate of adding the complexing agent solution is divided into a first step and a second step, and the flow rate of the complexing agent solution in the first step is greater than the flow rate of the complexing agent solution in the second step.
6. The method for preparing cobalt-rich hydroxide according to claim 5, characterized in that: At least one of the following conditions is met: A. The total mass concentration of metal ions in the cobalt-containing salt solution is 90 g / L to 140 g / L; B. the cobalt-containing salt solution further comprises at least one of Al, Ni, Mn, Mg, Ti, Zr, Mo, Cr, B, La, Y, Nb and Er; C. the precipitant solution is a sodium hydroxide solution; D. the mass concentration of the precipitant solution is 240 g / L to 440 g / L; E. the complexing agent solution is ammonia water and / or ethylenediamine solution; F. The mass concentration of the complexing agent solution is 10g / L to 30g / L; G. The base liquid is a mixture of pure water, the precipitant solution and the complexing agent solution, and the volume ratio of the water, the complexing agent solution and the precipitant solution is V 水 :V 络合剂 :V 沉淀剂 =(20~120):(0~2.5):1; H. The volume of the bottom liquid is 20v% to 50v% of the volume of the reactor; I. In the coprecipitation reaction, the flow rate of adding the cobalt-containing salt solution is 6% / h-30% / h of the volume of the reactor; J. In the coprecipitation reaction, when the precipitant solution and the cobalt-containing salt solution are added, the mass ratio of the precipitant in the precipitant solution to the metal element in the cobalt-containing salt solution is (1.25-1.65):1; K. The flow rate of the complexing agent solution in the first step is 2.5% / h-6.0% / h of the volume of the reactor, and the flow rate of the complexing agent solution in the second step is 0-1.5% / h of the volume of the reactor; L. The time for adding the complexing agent solution in the first step and the second step is independently 0.2h-2.5h; M. The stirring frequency is 40Hz-50Hz; N. The temperature of the coprecipitation reaction is 30°C to 60°C; O. The washing liquid used in the washing is pure water, and the washing temperature is 50°C to 75°C; P. The drying temperature is 80°C to 110°C and the drying time is 8h to 15h; Q. The pulverization is divided into the first pulverization and the second pulverization. The first pulverization is performed by using a disc nest mill and then passing through a 60-100 mesh sieve. The second pulverization is performed by using a jet mill. The feeding frequency of the second pulverization is 5Hz-8Hz.
7. A cobalt-coated positive electrode material, characterized in that: The secondary particles of the cobalt-coated positive electrode material include a matrix and a coating layer, the matrix includes the positive electrode material, and the raw material of the coating layer includes the cobalt-rich hydroxide according to any one of claims 1 to 4.
8. A method for preparing a cobalt-coated positive electrode material according to claim 7, characterized in that: include: The positive electrode material is mixed with the cobalt-rich hydroxide and then sintered to obtain the cobalt-coated positive electrode material.
9. The method for preparing a cobalt-coated positive electrode material according to claim 8, characterized in that: At least one of the following conditions is met: A. The average particle size D50 of the cobalt-coated positive electrode material is 10 μm-15 μm; B. The amount of the cobalt-rich hydroxide added is 0.01wt%-5wt% of the positive electrode material; C. The mixing time is 30min to 60min; D. The sintering temperature is 600°C to 900°C; E. The sintering time is 5h to 12h.
10. A lithium ion battery, characterized in that: Including the cobalt-coated positive electrode material as described in claim 7.
Citation Information
Patent Citations
Positive electrode material precursor, positive electrode material and application
CN118108267A
Cited By
Characterization method for mixing uniformity of lithium cobalt oxide positive electrode material and application of characterization method
CN120927757A